Influence of Crop Rotation, Tillage System and Residue on Soil Chemical Changes for Ferralitic Soils in Western Kenya - Rotich , Edwin Kiprono; Kibet Serem , Cornelius (African Journal of Education,Science and Technology (AJEST), 2017)
The bottom line of traditional farming systems in sub-Saharan Africa is primarily mining of soil nutrients. Declining soil fertility is caused by continuous cropping without nutrient inputs; depletion of soil nutrients and loss of organic matter, which has resulted in declining crop yield. To mitigate some of the practices causing reduced soil fertility, an on-farm experiment was conducted at Nyabeda in Siaya District, Nyanza Province, Western Kenya region to determine the effects of crop rotation, tillage system and crop residue management on the changes in soil pH, organic carbon, N levels and available soil P. A split-split plot experimental design was set up with crop rotation (maize with soy-beans) as main plots, tillage system (minimum tillage and conventional tillage) as sub-plots and crop residue management (with and without crop residue) as sub-sub plots for three consecutive seasons. At each planting, all plots received 60 kg of P2O5/ha and 60 kg of K2O/ha. Results for the three seasons indicated slight decrease in soil acidity, increase in soil organic carbon, soil total nitrogen and available soil P (p≤0.001) with rotation system where crop residue was returned, against control experiment of mono-cropping system without addition of crop residue. In 2004LR, tillage + residue significantly (p=0.014) contributed to soil pH variation. Slight increase in soil N suggests higher capacity for N fixation and mineralization in soils under rotation than monoculture in maize cropping. Rotation of maize and legumes under conventional tillage with crop residue addition may be envisaged as option for farmers to adopt in order to benefit from reduced input costs, improved soil fertility and enhanced food security.